Cultura de calidad en centros nocturnos y bares en México. Caso puerto de Veracruz (2015)
The tourism sector has been increasingly booming recently, and the competition has been a topic widely discussed. Quality is an important element that increases the competitiveness in bars and nightclubs, and in it, the staff of the company is a key player. Staff participation in the design of atmosphere, service and marketing elements, causes an increase in the competitiveness of companies in this industry to directly influence the consumer experience of customers as well as indirectly through previous experience, training of positive expectations and strengthening for recommendations from other customers. In the case of Veracruz, the industry has developed a culture of quality through learning the tastes and preferences of customers, allowing the development of social culture and economic activity internationally recognized.